2012
DOI: 10.4236/ojs.2012.22027
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effect of Food Habit, Lifestyle and Daily Trip on Physical and Mental Status of Subjects at Islamic University in Kushtia, Bangladesh

Abstract: This is a qualitative (study that used framework analysis) to examine by interviews among University personnel who live inside and outside the Islamic University campus in Kushtia, Bangladesh. In the present study, we found that subjects who live inside of the University feel better physically and mentally than the nonresident subjects. It was found that residents are more fit and feel better during and after class time. Resident subjects have less stress and maintain balanced diet for which they have good ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Local or resident population has less stress and disease level as compared to nonresident or hostelites. Locals have good dietary habits which ensures them a better lifestyle [68,74]. The association between physical activities and fruits and vegetable intake is beneficial for the mentally ill [66].…”
Section: Discussionmentioning
confidence: 99%
“…Local or resident population has less stress and disease level as compared to nonresident or hostelites. Locals have good dietary habits which ensures them a better lifestyle [68,74]. The association between physical activities and fruits and vegetable intake is beneficial for the mentally ill [66].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study showed that lifestyle in domains of nutrition, perceived stress, and unhealthy behavior were different between PMS and non-PMS groups. Nutritional habits are one of the lifestyle dimensions that influence physical health status ( 34 ). Our study results showed that the mean consumed amount of various foods was significantly different between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Pilot study was carried out between the 2nd January to January 21 of 2015, on (10) nurse who work in maternity department to determine the reliability of questionnaire and content validity was carried out through the 17 experts. Table (2) Shows that the half of study sample (51%) was at age group (30-39) years while the lowest percentage (15%) of them group age between (40-49) ; with the mean age and SD was (32 ± 8) years.…”
Section: Methodsmentioning
confidence: 97%
“…Food intake is focused progressively on sugar, fast food, and soft drinks. This unhealthy eating habits and lack of exercise leads to PCOS as well (2) . By royal college of obstetrician and gynecologists and the American college of obstetrician gynecologists the clinical feature of PCOS are irregular menstrual cycle or may be absent, hirsutism, loss of head hair, obesity, difficult to be pregnant or may be infertile, acne and oily skin (3,4) .…”
Section: Introductionmentioning
confidence: 99%